Investigation of the Mechanical Properties of Engineered Cementitious Composites with Low Fiber Content and with Crumb Rubber and High Fly Ash Content. Issue 5 (May 2019) - Noorvand, Hassan; Arce, Gabriel; Hassan, Marwa; Rupnow, Tyson; Mohammad, Louay N.
Engineered cementitious composites (ECCs) are a type of micromechanically-designed cementitious composite reinforced with a moderate volume fraction of short fiber, typically 2% by volume. ECCs form steady-state multiple cracking that considerably improves the tensile strength and ductility of traditional concrete. In this study, the properties of matrix and the interface of ECCs were tailored through the use of crumb rubber, different types of sand, and different replacement levels of cement with fly ash. The study examined the effect of sand replacement with crumb rubber (20% by volume), two types of river sands (coarse and fine), increasing the content of class F fly ash (up to 75% cement replacement), and low fiber content (1.75%) on the mechanical properties of ECCs. Compressive strength, uniaxial tensile, and third-point bending tests were performed to characterize the properties of ECC mixes. Experimental results demonstrated that increasing fly ash content and using crumb rubber favored ductility of the composites. However, higher fly ash contents and a low water-to-binder (W/B) ratio produced lower strengths as these limited the pozzolanic reaction of fly ash making it act partially as a filler. While incorporation of crumb rubber showed adverse effects on the tensile strength of ECC materials (up to 26% decrease), the tensile ductility of ECC materials improved significantly (up to 434% improvement). Moreover, the implementation of different types of sand produced minor effects on the mechanical properties of ECCs. Overall, a tradeoff between the strength and ductility of the composites was detected, which highlights the implications of matrix/interface tailoring in the overall performance of ECC.